Prevalence of depression and anxiety among chronic obstructive pulmonary disorder patients and its impact on the severity of the disease - Kamini, B; Gopinath, TT; Balamurugan, S; Arun, Jayakumar U; Narayanan, Harish (Asian Journal of Medical Sciences, 2022)
Background: There is high prevalence of anxiety and depression in chronic obstructive pulmonary disease (COPD) patients, leading to habits such as smoking. Aims and Objectives: This study aims to relate quantitatively, the contribution of anxiety and depression on prognosis, smoking, and stage of the disease. Materials and Methods: This cross-sectional study was conducted over a period of 3 months on 50 male COPD patients, aged 40–70 years. Patients were recruited to participate in the study after obtaining informed consent and were administered a questionnaire. They were subjected for detailed clinical examination, chest-X ray. CAT, BODE, GOLD stage, MADRS, and HAM-A were calculated and submitted for statistical analysis. Results: Depression had more influence on smoking rather than anxiety. There was no contributing influence by age. Conclusion: Clinicians should be encouraged to concentrate more on addressing depression rather than anxiety.